Improving the Skills of Demand Function Counting and Demand Curve Drawing Using Drill Method and Think Pair Share (TPS) (Dinamika Pendidikan, 2016)
This research aims to determine whether there is an increased of demand function counting and demand curve drawing using drill method and think pair share. It was a classroom action research that used drill and think pair share learning methods. The subjects of the research were students at class X IPS 4 in Senior High School 11 Semarang. Data were analyzed by using the simple descriptive statistics analysis with the mean of the evaluation result. Findings show that the mean of drill and think pair share learning methods in Class X IPS 4 Senior High School Negeri 11 Semarang was 72.94 and 76.10 at the pre-cycle. The study completeness was only by 13 students (39%). After conducting the first cycle, there was an improvement for 78.06 and 89.04. The study completeness was 18 students (55%). In the second cycle, students’ learning outcomes increased up to 95.76 and 99.29 with learning completeness was 33 students (100%).